2017
DOI: 10.1159/000457133
|View full text |Cite
|
Sign up to set email alerts
|

Upper Urinary Tract Tumors: Which Diagnostic Methods Are Needed?

Abstract: Objectives: We reviewed the data of patients with upper urinary tract (UUT) tumors to evaluate the effectiveness of diagnostic procedures. Methods: This retrospective study evaluated tumor characteristics, imaging procedures, epidemiological and follow-up data of 113 patients. We analyzed the importance of non-invasive and endoscopic diagnosis in addition to imaging as well as the influence of stage and grade on recurrence rate. Results: Most tumors were urothelial carcinomas (92.9%). The cardinal symptoms wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Brown et al [41] conducted a retrospective study of 184 UTUC patients undergoing RNU and found that 100%, 71.7%, and 33.8% of G1, G2, and G3 tumors, respectively, were superficial. Maruschke et al [7] reported similar results, although a larger proportion (88%) of the G3 tumors was invasive. Holmäng and Johansson [42] recut and re-evaluated 555 UTUC specimens from patients with no previous or concomitant bladder cancer.…”
Section: Diagnostic Workupmentioning
confidence: 70%
See 2 more Smart Citations
“…Brown et al [41] conducted a retrospective study of 184 UTUC patients undergoing RNU and found that 100%, 71.7%, and 33.8% of G1, G2, and G3 tumors, respectively, were superficial. Maruschke et al [7] reported similar results, although a larger proportion (88%) of the G3 tumors was invasive. Holmäng and Johansson [42] recut and re-evaluated 555 UTUC specimens from patients with no previous or concomitant bladder cancer.…”
Section: Diagnostic Workupmentioning
confidence: 70%
“…CTU has higher sensitivity than intravenous urography for diagnosing UTUC [7]. In patients with contraindication for use of contrast medium, magnetic resonance urography can be an option.…”
Section: Diagnostic Workupmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the selected articles from 2007 to 2021, four studies were retrospective cohort studies (28,30,41), and the remaining were case-control studies (29,(42)(43)(44)(45)(46). There were four studies from China (28,42,45), two studies from America (29,41), one study from Germany (43), two studies from Japan (30,46), and one study from Spain (44). In these studies, nine of them involved the risk of high-grade UUT-UC (28)(29)(30)(41)(42)(43)(44)(45).…”
Section: Meta-analysis Of the Correlation Between Preoperative Positive Urine Cytology And Tumor Malignant Biological Behavior For Uut-ucmentioning
confidence: 99%
“…Imaging approaches include CT and MRI with contrast, and cystoscopy or retrograde imaging followed by diagnostic ureteroscopy. These techniques are of limited accuracy in identifying upper tract lesions [ 159–161 ]. For example, white light URS for UTUC diagnosis is only 53% specific for malignant lesions, misdiagnosis can lead to unnecessary radical surgery or a missed opportunity for proper cure [ 160 ].…”
mentioning
confidence: 99%